Procedural justice, relative deprivation, and intra-team knowledge sharing: The moderating role of group identification - Wan, Jin; Qin, Mingyue; Zhou, Wenjun; Zhou, Haiming; Li, Pingping (Frontiers in Psychology, 2023)
How to promote employees' knowledge-sharing behaviors has become a focus of managers and researchers. Based on the theory of relative deprivation, this study explored the mechanism of organizational procedural justice on employees' intra-team knowledge sharing, as well as the mediating role of relative deprivation and the moderating role of group identification. A path analysis was conducted on 416 valid questionnaire data, and the results revealed that: (1) Procedural justice has a positive effect on intra-team knowledge sharing; (2) Both group relative deprivation and individual relative deprivation play a mediating role between procedural justice and intra-team knowledge sharing, but they have opposite effects. Procedural justice reduces both group relative deprivation and individual relative deprivation, but individual relative deprivation decreases employees' intra-team knowledge sharing, while group relative deprivation increases it. (3) Group identification has an enhancing moderating effect on the relationship between group relative deprivation and intra-team knowledge sharing, while the moderating effect on the relationship between individual relative deprivation and intra-team knowledge sharing is not significant. Therefore, enterprises should make procedures such as performance appraisal and salary allocation justify and transparent to reduce individual relative deprivation, but should moderately trigger group relative deprivation flexibly according to the situation, while enhancing employee group identification through cultural construction.